Social Computing with Microsoft SharePoint 2007: Implementing Applications for SharePoint to Enable Collaboration and Interaction in the Enterprise ( - Draper Stacy; Schwartz Brendon; Ranlett Matt (American : Wrox, 2009)
This book covers the major concepts, applications, and implementations of social computing and shows how they are built with SharePoint 2007 today. As you noticed earlier, this is a fast-moving area of computing. Where SharePoint 2007 does not have the capability today, we made sure and explained how you could extend SharePoint 2007 with open source or products you can purchase. We did not cover every product on the market, but we gave you any idea of what you can look for when you are trying to extend SharePoint.
The first two chapters provide the introduction for people new to social computing and how people will have to manage a social computing project. The following chapters break out each concept into a chapter to make it easy to get up to speed and understand what the topic is about.
Chapter 1 provides the introduction to what social computing is and the concepts behind social computing applications and discusses some of the technologies your organization might use to implement these concepts.
Chapter 2 describes how to build a successful project around social computing. This chapter takes you through steps that can make your team more successful, discusses the adoption of the application, and points out pitfalls that may get in your way to avoid them.
Chapter 3 discusses content tagging as one of the fundamental pieces of social computing. This chapter shows what content tagging is and how to use it to effectively build a solution with more visibility.
Chapter 4 demonstrates how to use wikis to build solutions for your organization and gives you hands-on examples of what the wiki can do for your company.
Chapter 5 covers the popular topic of blogs. This chapter shows you how to set up your own blog for your organization as well as discuss why you would even want a blog.
Chapter 6 delves into RSS and shows you what the XML is all about. This chapter covers what RSS is and how to consume it in your organization to successfully increase communication.
Keywords: Microsoft; SharePoint 2007